Pemodelan Fuzzy Time Series Cheng untuk Meramalkan Nilai Ekspor Migas di Indonesia - Engki Dulfitri Eha; Suwanda (UNISBA Press, 2023)
Abstract. Forecasting is useful for predicting future events which include the short, medium and long term. The data commonly used is time series data which is a collection of data that is arranged at a certain time continuously. There are several methods in the analysis of time series data, namely the traditional method (ARIMA) and Fuzzy time series. The fuzzy times series method is proven to be able to improve traditional methods such as handling data fluctuations, uncertainty of data subjectivity. With the privilege of not requiring the fulfillment of the assumption test. This thesis will discuss the Fuzzy time series cheng which is the development of the fuzzy time series chen and yu which can minimize forecasting errors. The Cheng's Fuzzy time series method has been applied to the value of Indonesia's oil and gas exports based on data for 1975-2022 with the forecast model obtained with a MAPE of 19.7668%. From the results of the forecasting model obtained in 2023 it is estimated that the value of Indonesia's oil and gas exports will be 15,215.9182 (million US), experiencing a decrease of 803,7818 (million US) when compared to the export value in 2022 of 16,019.7 (million US) . Abstrak. Peramalan berguna untuk memprediksi kejadian yang akan datang yang meliputi jangka pendek, menengah dan panjang. Data yang biasanya digunakan adalah data deret waktu yang merupakan kumpulan data yang disusun pada waktu tertentu secara terus menerus. Ada beberapa metode dalam analisis data deret waktu yaitu metode tradisional (ARIMA) dan Fuzzy time series. Metode fuzzy times series telah terbukti dapat memperbaiki metode tradisional seperti menangani fluktuasi data, ketidakpastian subjektivitas dalam data. Dengan keistimewaan tidak membutuhkan pemenuhan uji asumsi. Dalam skripsi ini akan di bahas Fuzzy time series cheng yang merupakan pengembangan dari Fuzzy time series chen dan yu yang dapat memperkecil kekeliruan peramalan. Metode Fuzzy time series cheng telah di terapkan pada nilai ekspor migas Indonesia berdasarkan data dari tahun 1975-2022 dengan diperoleh model ramalan dengan MAPE sebesar 19.7668%. Dari hasil model peramalan yang diperoleh pada tahun 2023 diperkirakan nilai ekspor migas Indonesia sebesar 15,215.9182(juta US), mengalami penurunan sebesar 803.7818 (juta US) jika dibandingkan dengan nilai ekspor tahun 2022 sebesar 16,019.7 (juta US).